2006
DOI: 10.1111/j.1439-0434.2006.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Species Colonizing Spears and Forming Mycotoxins in Field Samples of Asparagus from Germany and Poland

Abstract: The occurrence of Fusarium spp. and associated mycotoxins in asparagus spears was evaluated in Poland in 2002 and 2003 and in Germany in 2002. Spears of two cultivars, Eposs and Gijnlim, were collected from two locations in Poland, Swidwowiec and Poznan, on sandy and sandy loam soil, respectively. Fusarium oxysporum and F. proliferatum were detected at an average incidence of 38.3% and 15.8% in the spear sections sampled, respectively. In stands of 11 (tested) cultivars of asparagus sampled in Germany on sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
4
24
0
1
Order By: Relevance
“…There is also evidence that fumonisins occur in other crops such as sorghum, white beans, adzuki beans, mung beans, wheat, barley, soybean, asparagus spears, figs, black tea and medicinal plants (Blok & Bollen, 1995;Karbancioglu-Güler & Heperkan, 2009;Liu et al, 2005;Martins et al, 2001;Omurtag & Yaziciog ˇ l u, 2004;Weber et al, 2006;Wong & Jeffries, 2006). Moreover, in Polish asparagus spears with brown spots and those without disease symptoms the presence of fumonisin B 1 was found within the concentration range of 0.16e152.68 ng g À1 .…”
Section: Analytical Methods For Identification Of Fumonisinsmentioning
confidence: 87%
“…There is also evidence that fumonisins occur in other crops such as sorghum, white beans, adzuki beans, mung beans, wheat, barley, soybean, asparagus spears, figs, black tea and medicinal plants (Blok & Bollen, 1995;Karbancioglu-Güler & Heperkan, 2009;Liu et al, 2005;Martins et al, 2001;Omurtag & Yaziciog ˇ l u, 2004;Weber et al, 2006;Wong & Jeffries, 2006). Moreover, in Polish asparagus spears with brown spots and those without disease symptoms the presence of fumonisin B 1 was found within the concentration range of 0.16e152.68 ng g À1 .…”
Section: Analytical Methods For Identification Of Fumonisinsmentioning
confidence: 87%
“…In an earlier report we indicated that F. oxysporum was frequently found in asparagus spears contaminated with FBs (Weber et al 2006); however, according to the available literature and taking into consideration low concentration levels and sporadic occurrence of the toxins, we concluded that F. oxysporum is not the producer of FBs. Those results were confirmed by later studies (Waskiewicz et al 2010), indicating very low (close to the detection limit) levels of FB in the fungus culture.…”
Section: Introductionmentioning
confidence: 87%
“…Both F. proliferatum and F. oxysporum are known as the species causing stem and crown rot of asparagus (Weber et al 2006;Waskiewicz et al 2008). F. proliferatum can form a variety of mycotoxins including fumonisins (FBs), beauvericin (BEA) and moniliformin (MON) (Shephard et al 1990), while F. oxysporum is mainly recognized as a MON producer (Logrieco et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…in abhängigkeit von den jeweiligen Standortbedingungen treten dabei weltweit am häufigsten F. oxysporum Schlecht. und F. proliferatum (Matsushima) Nirenberg auf (Blok und Bollen 1995;elmer et al 1996;Goßmann et al 2001Goßmann et al , 2005Goßmann et al , 2008logrieco et al 1998;Weber et al 2006). Fäulen an den Wurzeln, den rhizomen und der Stängelbasis, irreversiblen Welken und Degenerationen, sowie Mykotoxine, die durch diese Fusarium-arten gebildet werden können, bedingen ertragsminderungen in Quantität und Qualität bei Spargel.…”
Section: Abstract Fusarium Oxysporum · Fusarium Proliferatum · Asparaunclassified